2010
DOI: 10.2202/1935-1682.2541
|View full text |Cite
|
Sign up to set email alerts
|

Household Demand for Broadband Internet in 2010

Abstract: This paper uses data from a nationwide survey administered during late 2009 and early 2010 to estimate a random utility model of household preferences for broadband Internet service. Reliability and speed are important service characteristics: the representative household is willing to pay $20 per month for more reliable service; $45 for an improvement in speed from slow to fast; and $48 for an improvement in speed from slow to very fast. A representative household would be willing to pay $79 per month for a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 0 publications
3
33
0
Order By: Relevance
“…Cadman and Dineen (2008) indicated that the pace of broadband penetration in the OECD is highly affected by income, with an increment of 1% in income resulting in an increment of 0.78% in demand. This is in line with the study by Rosston and Savage (2010). While, Horrigan (2009) argued that broadband Internet service was adopted by 63 percent of households as of 2009, which differed by variables such as income, age, and education.…”
Section: Literature Reviewsupporting
confidence: 80%
“…Cadman and Dineen (2008) indicated that the pace of broadband penetration in the OECD is highly affected by income, with an increment of 1% in income resulting in an increment of 0.78% in demand. This is in line with the study by Rosston and Savage (2010). While, Horrigan (2009) argued that broadband Internet service was adopted by 63 percent of households as of 2009, which differed by variables such as income, age, and education.…”
Section: Literature Reviewsupporting
confidence: 80%
“…Using a large sample of individuals, Rosston et al (2010) studied this phenomenon comparing experienced users with inexperienced users and estimated their willingness to pay, which is represented by the marginal utility of changing from one Internet service to another with higher interconnection speed. They included several measures in their analysis: cost, connection speed, reliability, use of Internet away from home, watching high definition content, interaction with health specialists and being able to perform free videophone calls.…”
Section: Stylized Factsmentioning
confidence: 99%
“…Several additional papers (Dutz et al 2009;Rosston et al 2010;Greenstein and McDevitt 2011) estimate the economic value of broadband internet, but without disaggregated decisions or usage-based pricing. Hitt and Tambe (2007) show that broadband adoption increases internet usage by 1,300 minutes per month, suggesting a strong preference for content that requires high bandwidth.…”
Section: Related Literaturementioning
confidence: 99%